Searchfor star cluster age gradients across spiral arms of three LEGUS disc galaxies. Issue 3 (16th May 2018) - Shabani, F; Grebel, E K; Pasquali, A; D'Onghia, E; Gallagher, J S; Adamo, A; Messa, M; Elmegreen, B G; Dobbs, C; Gouliermis, D A; Calzetti, D; Grasha, K; et al.
ABSTRACT: One of the main theories for explaining the formation of spiral arms in galaxies is the stationary density wave theory. This theory predicts the existence of an age gradient across the arms. We use the stellar cluster catalogues of the galaxies NGC 1566, M51a, and NGC 628 from the Legacy ExtraGalactic UV Survey (LEGUS) program. In order to test for the possible existence of an age sequence across the spiral arms, we quantified the azimuthal offset between star clusters of different ages in our target galaxies. We found that NGC 1566, a grand-design spiral galaxy with bisymmetric arms and a strong bar, shows a significant age gradient across the spiral arms that appear to be consistent with the prediction of the stationary density wave theory. In contrast, M51a with its two well-defined spiral arms and a weaker bar does not show an age gradient across the arms. In addition, a comparison with non-LEGUS star cluster catalogues for M51a yields similar results. We believe that the spiral structure of M51a is not the result of a stationary density wave with a fixed pattern speed. Instead, tidal interactions could be the dominant mechanism for the formation of spiral arms. We also found no offset in the azimuthal distribution of star clusters with different ages across the weak spiral arms of NGC 628.